Saint George and the dragon : a golden legend - Hodges, Margaret, 1911-2005 (Little, Brown, 1984)
Retells the segment from Spenser's The Faerie Queene, in which George, the Red Cross Knight, slays the dreadful dragon that has been terrorizing the countryside for years and brings peace and joy to the land.